If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+7x-2=2x+12
We move all terms to the left:
2x+7x-2-(2x+12)=0
We add all the numbers together, and all the variables
9x-(2x+12)-2=0
We get rid of parentheses
9x-2x-12-2=0
We add all the numbers together, and all the variables
7x-14=0
We move all terms containing x to the left, all other terms to the right
7x=14
x=14/7
x=2
| 3(6p-1)-11p=45 | | A=9/5(h-1) | | 1.5y-7=0.5 | | 6x–3(6–5x)+3x=10–4(2–x) | | 20=3r-4 | | (x+25)(x-24)=0 | | 5x-7=11x-2x | | 9(m-3)+3m-7m=43 | | 16-32b+12=-196 | | d-8/−2=12 | | 16.78+10.18-3.1v=-17.69-7.8v | | 9x-7=-19 | | -19-8u=15-14u+20 | | 15=10d–15 | | -2/5=4x-1/7 | | 17.1p-17.9p+9.57=1.07-17.8p | | 2(3x+4)=6x-7 | | 3c-20+6c=10+6c | | (x-25)(x+24)=0 | | (x-25)(x+24)=6000 | | 7/2x=5/6 | | 18f-20f+18=-4f-10 | | (x-25)(x+24)=600 | | (x-25)(x+13)=325 | | 1=-1+t6 | | 19x=-12x | | 25=-2r+3 | | -9.1d+10.8=6.02-2.2d+19.96 | | 9=3(q+8) | | -h-18=18+4+4h | | -6q-1+7q=2q+14 | | 4=2/3(r-6) |